Natural and other experiments: the secret history of the war on cancer - Lee Davis, Devra (European Journal of Oncology and Environmental Health, 2008)
In 1936, the world’s leading cancer scientists gathered in Brussels for the Second International Congress of the Scientific and Social Campaign Against Cancer, exchanging information on the capacity of benzene, radiation, hydrocarbons, synthetic hormones and sunlight to induce cancer experimentally and in humans. The nature of evidence on environmental causes of cancer considered at that gathering ranged from experimental studies to observations that “uniovular” (monozygotic) twins did not develop the same cancer much of the time. As the world turned to war-time footing, concerns about the long-term consequences for health of workplace and other exposures were eclipsed by immediate threats – a condition that haunts thinking about cancer to this day. The sowing of doubt regarding the relevance of experimental science to explaining the hazards of tobacco provided a model that was easily extended to many other modern health dangers, including those of the workplace and general environment.